The transformative potential of boundary spanners: a narrative inquiry into preservice teacher education and professional development in an NCLB-impacted context. - Whitenack, David Alan; Swanson, Patricia E. (Education Policy Analysis Archives, 2013)
This narrative inquiry uses pedagogic discourse theory and organization theory to frame pre-service teacher education and in-service professional development initiatives in a school district facing tensions related to the No Child Left Behind Act of 2001. Implications for similar future initiatives are considered.